Email Tracking Beacon : Concerns and Solutions - Mohammad, Hossin; Yew, L. K. (IJERT, 2019)
Email tracking is an essential way to manage the recipients’ responses especially in marketing and customer relationship management (CRM). However, the usage of email tracking beacons for monitoring purposes has brought the negative impacts to the security and privacy issues. This paper reveals the working flow of email tracking beacons and discuss the issues regarding to the usage of email beacons. Besides, some of the existing solutions have been reviewed to prevent the email user from being tracked by the email sender. This paper also proposed an alternative solution for tracking email responses without using the email tracking beacon.